Activity of Averrhoa Bilimbi L Leaf Extract as Denture Cleaner Towards The Number of Colonies of Candida Albicans in Heat Cured Resin with a 30 Minutes Period - Idamawati; M. Simanjuntak, Rouli Natasia; Molek; Listyaning Kartiko Kinasih (Biomedical Journal of Indonesia, 2021)
Denture stomatitis is a chronic inflammatory condition of the oral mucosa thatgenerally occurs in users of removable dentures. The cause is multifactorialbut is often associated with the presence of Candida albicans. The mucosawhich is covered by the denture base also reduces the function of saliva whichfunctions as a cleanser for the oral cavity and results in food wasteaccumulating and microorganisms such as Candida albicans can increase innumber. Candida albicans is a normal flora of the oral cavity which is anopportunistic pathogen. The starfruit plant (Averrhoa billimbi l) is a naturalingredient that can be used as an antifungal agent. The aim was to determinethe ratio of the effectiveness of starfruit leaf extract (Averrhoa billimbi) betweenthe concentrations of 12.5%, 25%, 50%, 100%, control + (Clorhexidine) andcontrol - (Aquadest) in reducing the number of Candida albicans colonies. Thetest method used the dilution method, the colony count of Candida albicansusing a spectrophotometer. The results of the one way ANOVA statistical testresulted in a significance value of p = 0.000 (p <0.05) which means that thereis a difference in the average concentration of Candida albicans between theextract concentrations of 12.5%, 25%, 50%, 100%, control + and control. -namely 6.78 ± 0.35, 6.27 ± 0.21, 4.89 ± 0.29, 1.01 ± 0.18, 0.59 ± 0.19 and 9.13± 2.28 in inhibiting growth Candida albicans and this was confirmed by theTukey HSD posthoc test. The conclusion of this study is that there is adifference between the antifungal effectiveness of starfruit leaf extract(Averrhoa billimbi) concentrations of 12.5%, 25%, 50% and 100% in inhibitingthe growth of Candida albicans colonies.